Der Satz im Koreanischen - Kostrzewa, Frank (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The Korean language is an agglutinative language belonging to the Ural-Altaic language family, which follows a subject-object-verb-structure. The verbs are followed by suffixes which denote tense, aspect, mode and honorific forms. Nouns, pronouns and other non-verbal parts of speech are followed by particles which mark the role of the corresponding parts of speech in the sentence. The Korean language does not possess prepositions. Thus, the major part of grammatical relations and other functional connections, which in English are marked by prepositions as well as subordinating or coordinating conjunctions, is expressed by postpositional particles. The marking of subjects by postpositions allows subjects to appear in different parts of a sentence than the initial position. A typical Korean sentence follows the subsequent pattern: 1st Time adverbials 2nd Local adverbial (Adverbial of Place) 3rd Subject-Noun phrase 4th Dative-Noun phrase 5th Modal adverbials 6th Object-Noun phrase 7th Verb
Keywords: Sentence; Korean Language; Subject-Object-Verb (S-O-V)-structure; verbs; suffixes; postpositional particles; patterns